Bis(phenolate)amine-supported lanthanide borohydride complexes for styrene and trans-1, 4-isoprene (co-)polymerisations12. Issue 27 (21st July 2015) - Bonnet, Fanny; Dyer, Hellen E.; El Kinani, Yassine; Dietz, Carin; Roussel, Pascal; Bria, Marc; Visseaux, Marc; Zinck, Philippe; Mountford, Philip
<x xml:space="preserve">Abstract</x> New bis(phenolate)amine-supported neodymium borohydride complexes and their previously reported samarium analogues were tested as catalysts for the polymerisation of styrene and isoprene.